Focused Ultrasound‐Augmented Delivery of Biodegradable Multifunctional Nanoplatforms for Imaging‐Guided Brain Tumor Treatment. Issue 4 (10th January 2018) - Wu, Meiying; Chen, Wenting; Chen, Yu; Zhang, Haixian; Liu, Chengbo; Deng, Zhiting; Sheng, Zonghai; Chen, Jingqin; Liu, Xin; Yan, Fei; Zheng, Hairong
Abstract: The blood brain barrier is the main obstacle to delivering diagnostic and therapeutic agents to the diseased sites of brain. It is still of great challenge for the combined use of focused ultrasound (FUS) and theranostic nanotechnology to achieve noninvasive and localized delivery of chemotherapeutic drugs into orthotopic brain tumor. In this work, a unique theranostic nanoplatform for highly efficient photoacoustic imaging‐ guided chemotherapy of brain tumor both in vitro and in vivo, which is based on the utilization of hollow mesoporous organosilica nanoparticles (HMONs) to integrate ultrasmall Cu2− x Se particles on the surface and doxorubicin inside the hollow interior, is synthesized. The developed multifunctional theranostic nanosystems exhibit tumor‐triggered programmed destruction due to the reducing microenvironment‐responsive cleavage of disulfide bonds that are incorporated into the framework of HMONs and linked between HMONs and Cu2− x Se, resulting in tumor‐specific biodegradation and on‐demand drug‐releasing behavior. Such tumor microenvironment‐responsive biodegradable and biocompatible theranostic nanosystems in combination with FUS provide a promising delivery nanoplatform with high performance for orthotopic brain tumor imaging and therapy. Abstract : A novel tumor‐microenvironment‐driven biodegradable HCu nanoplatform with photoacoustic imaging and on‐demand drug‐releasing performance, which is based on the integration of hollow mesoporous organosilica nanoparticles with ultrasmall Cu2− x Se nanoparticles, is successfully constructed. The excellent orthotopic brain tumor‐inhibition effect is achieved by concurrent use of HCu nanosystems and focused ultrasound‐induced blood brain barrier opening.